Activation of satellite cells and the regeneration of human skeletal muscle are expedited by ingestion of nonsteroidal anti‐inflammatory medication. Issue 6 (2nd March 2016) - Mackey, Abigail L.; Rasmussen, Lotte K.; Kadi, Fawzi; Schjerling, Peter; Helmark, Ida C.; Ponsot, Elodie; Aagaard, Per; Durigan, João Luiz Q.; Kjaer, Michael
ABSTRACT: With this study we investigated the role of nonsteroidal anti‐inflammatory drugs (NSAIDs) in human skeletal muscle regeneration. Young men ingested NSAID [1200 mg/d ibuprofen (IBU)] or placebo (PLA) daily for 2 wk before and 4 wk after an electrical stimulation‐induced injury to the leg extensor muscles of one leg. Muscle biopsies were collected from the vastus lateralis muscles before and after stimulation (2.5 h and 2, 7, and 30 d) and were assessed for satellite cells and regeneration by immunohistochemistry and real‐time RT‐PCR, and we also measured telomere length. After injury, and compared with PLA, IBU was found to augment the proportion of ActiveNotch1 + satellite cells at 2 d [IBU, 29 ± 3% vs. PLA, 19 ± 2% (means ± sem )], satellite cell content at 7 d [IBU, 0.16 ± 0.01 vs. PLA, 0.12 ± 0.01 (Pax7 + cells/fiber)], and to expedite muscle repair at 30 d. The PLA group displayed a greater proportion of embryonic myosin + fibers and a residual ~2‐fold increase in mRNA levels of matrix proteins (all P < 0.05). Endomysial collagen was also elevated with PLA at 30 d. Minimum telomere length shortening was not observed. In conclusion, ingestion of NSAID has a potentiating effect on Notch activation of satellite cells and muscle remodeling during large‐scale regeneration of injured human skeletal muscle.—Mackey, A. L., Rasmussen, L. K., Kadi, F., Schjerling, P., Helmark, I. C., Ponsot, E., Aagaard, P., Durigan, J. L. Q., Kjaer, M. Activation of satellite cells and the regeneration of human skeletal muscle are expedited by ingestion of nonsteroidal anti‐inflammatory medication. FASEB J. 30, 2266–2281 (2016). www.fasebj.org